Epigenetic condensates regulate chromatin activity and tumorigenesis - Bi Shi; Wei Li; Hao Jiang (Molecular & Cellular Oncology, 2021)
Alterations of epigenetic modulators are extensively associated with cancer, but their key molecular activities in cancer regulation are often unclear. We discovered that lysine demethylase 6A (KDM6A, also known as UTX) suppresses cancer by forming liquid-like condensates with lysine methyltransferase 2D (KMT2D, also known as MLL4) and regulating chromatin activity at multiple levels.